2015
DOI: 10.1016/j.biomaterials.2015.07.042
|View full text |Cite
|
Sign up to set email alerts
|

The use of covalently immobilized stem cell factor to selectively affect hematopoietic stem cell activity within a gelatin hydrogel

Abstract: Hematopoietic stem cells (HSCs) are a rare stem cell population found primarily in the bone marrow and responsible for the production of the body’s full complement of blood and immune cells. Used clinically to treat a range of hematopoietic disorders, there is a significant need to identify approaches to selectively expand their numbers ex vivo. Here we describe a methacrylamide-functionalized gelatin (GelMA) hydrogel for in vitro culture of primary murine HSCs. Stem cell factor (SCF) is a critical biomolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 83 publications
2
99
0
Order By: Relevance
“…Here, we describe the use of estradiol and progesterone to alter the individual and combined proangiogenic activities of endometrial epithelial and stromal cells (endoEpCs and endoSCs, respectively), as well as subsequent endothelial cell vessel formation, within a methacrylamide-functionalized gelatin (GelMA) hydrogel recently described by our laboratory. [14] All experiments were performed in three-dimensions, with cells encapsulated directly within the hydrogel matrix from the start of the experiment. Inspired by the temporal presentation of sex steroids within the native endometrium, we also explore a method using sex hormone binding globulin (SHBG) to sequester estradiol within the hydrogel as a means to alter residence time.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe the use of estradiol and progesterone to alter the individual and combined proangiogenic activities of endometrial epithelial and stromal cells (endoEpCs and endoSCs, respectively), as well as subsequent endothelial cell vessel formation, within a methacrylamide-functionalized gelatin (GelMA) hydrogel recently described by our laboratory. [14] All experiments were performed in three-dimensions, with cells encapsulated directly within the hydrogel matrix from the start of the experiment. Inspired by the temporal presentation of sex steroids within the native endometrium, we also explore a method using sex hormone binding globulin (SHBG) to sequester estradiol within the hydrogel as a means to alter residence time.…”
Section: Introductionmentioning
confidence: 99%
“…Primary murine Hematopoietic stem progenitor cells (HSPC) were extracted from the femur and tibia bone marrow of C57BL/6 female mice, age 4 -8 weeks (Jackson Labs). The bones were gently crushed with pestle and mortar, and washed with PBS + 5%FBS prior to filtration with a 40µm sterile filter [29,46]. The collected suspension was lysed with ACK lysis buffer (Invitrogen, Carlsbad, CA), and then rinsed with PBS/FBS.…”
Section: Hematopoietic Stem Cell Isolationmentioning
confidence: 99%
“…The LSK faction was collect in PBS + 25% FBS on ice and immediately used [19,29,46,[67][68][69][70].…”
Section: Hematopoietic Stem Cell Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell factor coupled to methacrylamide-functionalized gelatin gels (GelMA) has been used to analyze the influence on Lin − Sca-1 + c-kit + (LSK) cells with regard to maintaining more primitive HSC fractions, viability and expansion. It was shown that matrix-immobilized SCF is more selective in its ability to maintain primitive HSC fractions within a fully-3D hydrogel biomaterial as compared to soluble SCF in the media, likely due to exclusion of soluble SCFinduced differentiation [90]. A unique approach that made use of so-called inverted colloidal crystals (ICC) for the generation of polyacrylamide gels with a layer-by-layer-surface coating of DLL-1 notch ligand showed that when cultivating the mononuclear fraction, pre-erythrocytes and dendritic cells could be observed whereas when HSCs from cord blood were cultivated, T-cell lineage commitment and differentiation could be seen [91].…”
Section: Gel-based Systemsmentioning
confidence: 99%